2022
DOI: 10.1002/jcla.24387
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and mortality rate in COVID‐19 patients with hematological malignancies: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 82 publications
3
20
2
Order By: Relevance
“…The data regarding COVID-19 infection in acute leukemia patients is scarce, mainly on the wild (alpha) variant. Data showed that patients with acute leukemia reported having an increased risk of morbidity and mortality [ 9 , 15 ]. Our reported cases showed that acute leukemia patients could present with mild illness and have severe disease with the Omicron variant, as seen in case 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data regarding COVID-19 infection in acute leukemia patients is scarce, mainly on the wild (alpha) variant. Data showed that patients with acute leukemia reported having an increased risk of morbidity and mortality [ 9 , 15 ]. Our reported cases showed that acute leukemia patients could present with mild illness and have severe disease with the Omicron variant, as seen in case 2.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 disease is frequently associated with an elevated white cell count in patients with chronic lymphocytic leukemia, and mortality is related to age [ 7 , 8 ]. Previous studies showed that acute leukemia with SARS-CoV-2 infection had increased mortality [ 9 ]. However, data about the impact of the Omicron variant of the SARS-CoV-2 virus on patients with acute leukemia is small.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics for COVID-19 appear 1–14 days after infection, and most patients develop symptoms within 3–7 days [ 12 , 13 ]. Fever, cough, and dyspnea were the most common symptoms in patients with COVID-19 pneumonia [ 14 , 15 ], followed by the manifestation of lower respiratory tract infections [ 16 ]. By contrast, upper respiratory tract symptoms were less common in these patients, indicating that the cells targeted by the virus might be located in the lower airway [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The world has been fighting coronavirus disease 2019 (COVID-19) illness for nearly 2 years ( Koupaei et al, 2022a ; Naimi et al, 2022 ). COVID-19 was induced by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), which emerged in Wuhan, China ( Koupaei et al, 2021 ; Mahdizade Ari et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%